Market Basket Analysis Pada Mini Market Ayu Dengan Algoritma Apriori - Erlin Elisa (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2018)
Data mining is a technique to extract new information from the data warehouse, information is considered very important and valuable because by mastering the information so easily to achieve a goal, this makes everyone competing to obtain information, as well as on trading businesses such as minimarket Ayu in Kota Batam. Minimarket is located close to the home of the population, this certainly affects the level of sales, with the daily sales activities, sales transaction data will continue to grow, causing data storage is greater. Sales transaction data is only used as an archive without being put to good use. Basically the data set has very useful information. The analysis of market basket with Apriori Algorithm is one method of data mining which aims to find the pattern of association based on consumer spending pattern, so that it can be known what items are purchased simultaneously. The result of this research found that the highest support and confidence value is Oil and Milk with a support value of 42.85% and confidence of 85.71%.